Recent advances in the production, recovery and applications of polyhydroxyalkanoates - Gumel, A.M.; Annuar, Mohamad Suffian Mohamad; Chisti, Y. (Springer, 2013)
Polyhydroxyalkanoates (PHAs) are biodegradable and biocompatible polyesters that can potentially replace certain plastics derived from petroleum. PHAs can be produced using a combination of renewable feedstocks and biological methods. Native and recombinant microorganisms have been generally used for making PHAs via fermentation processes. As much as 90 % of the microbial dry mass may accumulate as PHAs. A range of PHAs has been produced using fermentation methods, including copolymers and block copolymers. Alternative production schemes based on genetically modified plants are becoming established and may become the preferred route for producing certain PHAs. Production in plants is likely to be inexpensive compared to production by fermentation, but it does not appear to be as versatile as microbial synthesis in terms of the range of products that may be generated. Cellfree enzymatic production of PHAs in vitro is receiving increasing attention and may become the preferred route to some specialty products. This review discusses the recent advances in production of polyhydroxyalkanoates by the various methods. Methods of recovering the polymer from microbial biomass are reviewed. Established and emerging applications of PHAs are discussed.